Optimization of Data Security Protection with Full SSL Inspection on AWS Using FortiGate Virtual Appliance - Yuma Akbar; Gipari Pradina Abdillah; Dadang Iskandar Mulyana; Sutisna Sutisna (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The expanding adoption of cloud services, particularly Amazon Web Services (AWS), has intensified challenges in protecting encrypted data traffic within network security frameworks. SSL/TLS protocols, widely utilized for data encryption, have become exploitation vectors for cyber adversaries as conventional security solutions lack the capability to scrutinize encrypted traffic effectively. The research addresses such security gaps by implementing Full SSL Inspection through Fortigate Virtual Appliance deployment within AWS cloud environments. The study examines cloud-based network architecture integrated with Fortigate systems, employing methodologies that encompass virtual appliance installation, SSL/TLS inspection feature configuration, and assessment of system effectiveness alongside performance impact evaluation. Research instruments include simulated cyber-attack scenarios targeting encrypted traffic patterns. Findings demonstrate that Full SSL Inspection significantly enhances threat detection capabilities within network traffic, albeit with measurable increases in system latency and computational overhead. The implementation of Fortigate Virtual Appliance proves effective in strengthening AWS data security postures. Research outcomes emphasize the necessity for configuration optimization to maintain security-performance equilibrium, positioning the solution as viable for organizations prioritizing data protection strategies